Assessment of disinfection of hospital surfaces using different monitoring methods - Adriano Menis Ferreira; Denise de Andrade; Marcelo Alessandro Rigotti; Margarete Teresa Gottardo de Almeida; Odanir Garcia Guerra; Aires Garcia dos Santos Junior (Revista Latino-Americana de Enfermagem, 2015)
OBJECTIVE: to assess the efficiency of cleaning/disinfection of surfaces of an Intensive Care Unit.METHOD: descriptive-exploratory study with quantitative approach conducted over the course of four weeks. Visual inspection, bioluminescence adenosine triphosphate and microbiological indicators were used to indicate cleanliness/disinfection. Five surfaces (bed rails, bedside tables, infusion pumps, nurses' counter, and medical prescription table) were assessed before and after the use of rubbing alcohol at 70% (w/v), totaling 160 samples for each method. Non-parametric tests were used considering statistically significant differences at p<0.05.RESULTS: after the cleaning/disinfection process, 87.5, 79.4 and 87.5% of the surfaces were considered clean using the visual inspection, bioluminescence adenosine triphosphate and microbiological analyses, respectively. A statistically significant decrease was observed in the disapproval rates after the cleaning process considering the three assessment methods; the visual inspection was the least reliable.CONCLUSION: the cleaning/disinfection method was efficient in reducing microbial load and organic matter of surfaces, however, these findings require further study to clarify aspects related to the efficiency of friction, its frequency, and whether or not there is association with other inputs to achieve improved results of the cleaning/disinfection process.